Metaverses: A new Frontier for Remote Software Development Teams - Aoki, Ayumi; Lima, Márcia; Rodrigues, Eriky; Galvão, Leandro; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
The remote work model is becoming more established in software companies. Despite its benefits, this shift brings challenges, such as asynchronous communication and a lack of social interactions. To overcome these obstacles, development teams are adopting metaverse environments. In this context, this research investigates the impact of using metaverse environments on the experience of members of remote software development teams. To this end, we conducted surveys and interviews with ten practitioners from three software development companies that use Gather.Town. The results indicate that metaverse environments such as Gather.Town facilitates collaboration in remote software development teams through social interaction, a sense of presence, and efficient communication, overcoming the limitations of traditional remote work, such as social isolation. This report demonstrates that using metaverse environments can enhance communication and collaboration in remote teams, providing a more integrated and efficient work experience.